SPECTRAL EXPANSION FOR SINGULAR BETA STURM-LIOUVILLE PROBLEMS - Bilender P. Allahverdiev; Hüseyin Tuna; Yüksel Yalçinkaya (Ural Mathematical Journal, 2024)
In this study, beta Sturm–Liouville problems are discussed. For such equations, the spectral function is established in the singular case. A spectral expansion is given with the help of this function.